Air Flow Characteristics and Behaviour of Main Rotor Blade of Remote Controlled Model Scale Helicopter - Ammoo, Mohd. Shariff bin; Awal, Ziad Bin Abdul; Koto, Jaswar (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2015)
The airflow through the main rotor blade system of a helicopter is still not exceedingly well understood owing to its obscurity in aerodynamics. It is prognosticated that helicopter wakes can be significantly greater than those formed by a fixed wing aircraft of the same weight. Nuisance incidents such as brownout & noises are engendered from rotor wake. Study through flow visualization plays a key role in understanding the airflow distinctiveness and vortex interaction of a helicopter rotor blade. Inspecting and scrutinizing the effects of wake vortices during operation is a great challenge and imperative in designing effective rotor system. This study aimed at finding a suitable method to visualize the main rotor airflow pattern of a remote controlled subscale helicopter and seek for the vortex flow at the blade tip. The experimental qualitative data is correlated with quantitative data to perform meticulous study on the airflow behaviour & characteristics along with its distinctiveness generated by the main rotor in various flight conditions. Simulation is also performed in similar conditions to bequeath with comparability between the flow visualization results. Several dissimilar flow patterns were identified throughout the blade span. At the centre of the main rotor hub, the presence of turbulent flow was perceived. This is because of the low energy of air pooled in this region. Conversely, an apparent straight streamline pattern in the middle portion of the rotor blade was noticed as the air in this section encompassed high kinetic energy.